2020
DOI: 10.1002/cam4.3683
|View full text |Cite
|
Sign up to set email alerts
|

AL amyloidosis: The effect of fluorescent in situ hybridization abnormalities on organ involvement and survival

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Another study conducted by Ozga et al described a broader definition of hyperdiploidy that included gains/ trisomies of 2 or more of any chromosome loci. In this study, 38% of patients harbored hyperdiploidy, which was confirmed to be associated with shorter PFS and OS in the multivariate analysis [17].…”
Section: Hyperdiploidysupporting
confidence: 73%
See 4 more Smart Citations
“…Another study conducted by Ozga et al described a broader definition of hyperdiploidy that included gains/ trisomies of 2 or more of any chromosome loci. In this study, 38% of patients harbored hyperdiploidy, which was confirmed to be associated with shorter PFS and OS in the multivariate analysis [17].…”
Section: Hyperdiploidysupporting
confidence: 73%
“…About 10-40% of AL patients cannot be detected to harbor any chromosome aberration by the MM's genetic probes. This patient group tends to have lower plasma cell burden, less severe cardiac involvement, longer progression-free survival (PFS) and overall survival (OS) [15][16][17]19], indicating that the absence of chromosome aberration in AL may be a favorable prognostic predictor of outcome.…”
Section: Normal Chromosome Profilementioning
confidence: 99%
See 3 more Smart Citations